Characterizing Erosion and Deposition in and Around Riparian Vegetation Patches: Complex Flow Hydraulics, Sediment Supply, and Morphodynamic Feedbacks - Andrew W. Tranmer; Un Ji; Myeonghui Ahn; Sang Hwa Jung; Elowyn M. Yager (Water Resources Research)
Abstract Riparian vegetation plays a fundamental role in alluvial channel evolution by modifying flow and sedimentation dynamics. To elucidate the roles of sediment supply, flow‐dependent transport capacity, and morphodynamic feedbacks on the evolution of emergent vegetation patches over a single hydrograph, we conducted two experiments with different reach‐scale sediment supplies: a high‐supply experiment (HSE) and low‐supply experiment (LSE). We measured flow velocities, bedload transport, and topographic changes around a full‐scale patch of live emergent willows in an outdoor laboratory flume. Erosion occurred in the patch‐adjacent channel areas irrespective of the sediment supply, whereas deposition within the patch interior was suppressed in the LSE and enhanced in the HSE. The magnitude of patch deposition in each experiment was controlled by the local sediment supply to the patch and local sediment mobility during each discharge in the hydrograph. The local sediment supply was affected by bed morphodynamics at the patch head, which modulated the reach‐scale sediment supply by redistributing the bedload in the channel. Sediment mobility within the patch was flow‐dependent and a function of velocity and turbulent kinetic energy. For different discharges, the velocity in the patch changed proportionally with the freestream velocity; however, the turbulent kinetic energy was more sensitive, being elevated compared with the freestream during high flows and inhibited at low flows. Therefore, deposition and erosion within vegetation patches are not simply functions of the reach‐scale sediment supply or patch flow characteristics, as is often assumed, but additionally depend on the local sediment supply to the patch interior.